THE ONTOLOGY OF THE HUMAN SELF IN THE QUR’AN AND ITS IMPLICATIONS FOR PHILOSOPHICAL ANTHROPOLOGY OF EDUCATION - Agustin, Maulid; Alfarizi, Moch Salman; Stang, Taufik Hidayat; Andri Nirwana (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
The conceptual crisis in modern education, which tends to view human beings in a reductionistic way, is limited to the rational and social dimensions, while the spiritual and transcendental aspects are ignored. The purpose of this study is to examine the nature of the human self in the perspective of the Qur'an by tracing the conceptual structure of nafs, qalb, 'aql, and rūḥ, and analyzing their implications for the philosophy of Islamic educational anthropology through a critical comparison with the theories of self-consciousness. The method used is a literature-based qualitative approach with philosophical-hermeneutic analysis and conceptual analysis. The results of the study show that the Qur'an views humans as multidimensional entities that unite rationality, morality, and spirituality in a relational awareness of God. This ontological concept of the Qur'an gave birth to the paradigm of the transcendental personality, the human self who is morally free but spiritually submissive to Divine values. Its philosophical implications for Islamic education are the need to build an integrated self-oriented humanistic-transcendental educational, through the processes of ta'aqqul (intellectual development), ta'dīb (moral formation), and tazkiyah (purification of the soul), in order to produce insān kāmil, a whole human being who is knowledgeable, civilized, and divinely aware.